PHYLLOCAULIS GAYI (PULMONATA: SYSTELLOMMATOPHORA): A NEGLECTED GRANIVORE IN CHILEAN TEMPERATE FORESTS? PHYLLOCAULIS GAYI (PULMONATA: SYSTELLOMMATOPHORA): ¿UN GRANIVORO DESCONOCIDO EN LOS BOSQUES TEMPLADOS DE CHILE? - Javier A. Simonetti; Audrey A. Grez; Ramiro O. Bustamante (Gayana, 2003)
Evidence is advanced suggesting that Phyllocaulis gayi, a large slug in the temperate forests of Chile, might be a significant but overlooked granivore. In a short-term experiment, up to 18% of seeds are preyed upon by P. gayi. The intensity of seed predation is significantly reduced in forest fragments Presentamos evidencia que Phyllocaulis gayi, una babosa de gran tamaño, podría ser un granívoro ignorado en los bosques templados de Chile. En experimentos de corto plazo, un 18% de las semillas son depredadas por P. gayi . La magnitud de la depredación es significativamente reducida en fragmentos de bosque